2004
DOI: 10.1152/jn.00553.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imaging of the Human Lateral Geniculate Nucleus and Pulvinar

Abstract: . In the human brain, little is known about the functional anatomy and response properties of subcortical nuclei containing visual maps such as the lateral geniculate nucleus (LGN) and the pulvinar. Using functional magnetic resonance imaging (fMRI) at 3 tesla (T), collective responses of neural populations in the LGN were measured as a function of stimulus contrast and flicker reversal rate and compared with those obtained in visual cortex. Flickering checkerboard stimuli presented in alternation to the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

36
175
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(216 citation statements)
references
References 74 publications
(91 reference statements)
36
175
5
Order By: Relevance
“…In fact, emotional modulation of subcortical structures induced by consciously seen stimuli was restricted to the right (contralateral) LGN. Activity in the right LGN for stimuli in the LVF is consistent with evidence that LGN neurons have receptive fields confined to the contralateral visual hemifield (43) and also provides an additional indication that GY kept steady fixation during the experiment, so that the stimuli fell only in the designated visual hemifield. This result is also in line with evidence that activation in the LGN of GY is related to consciously seen visual stimuli, but not to nonconscious visuomotor integration and blindsight (3), and probably reflects cortico-geniculate feedback from the ipsilateral V1.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, emotional modulation of subcortical structures induced by consciously seen stimuli was restricted to the right (contralateral) LGN. Activity in the right LGN for stimuli in the LVF is consistent with evidence that LGN neurons have receptive fields confined to the contralateral visual hemifield (43) and also provides an additional indication that GY kept steady fixation during the experiment, so that the stimuli fell only in the designated visual hemifield. This result is also in line with evidence that activation in the LGN of GY is related to consciously seen visual stimuli, but not to nonconscious visuomotor integration and blindsight (3), and probably reflects cortico-geniculate feedback from the ipsilateral V1.…”
Section: Discussionsupporting
confidence: 81%
“…To test the latter hypothesis, we examined activity in the superior colliculus and the pulvinar, identified anatomically according to criteria described in ref. 36. We compared activity during between-hemisphere and within-hemisphere attention conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical tracer studies in the monkey brain indicate that although ventral pulvinar neurons predominantly represent the contralateral hemifield (13,19,39) neurons with large, bilateral receptive fields have been recorded from cells within macaque lateral (ventral) pulvinar (40). Similarly, fMRI evidence in healthy humans (27,30) suggests that, as in the monkey, human pulvinar may have neurons with large receptive fields that can influence attentional competition across the entire visual field. However, a more recent fMRI study reported activation within ventral pulvinar only for contralateral events (41).…”
Section: Discussionmentioning
confidence: 99%
“…Heretofore, neuropsychological studies in patients with pulvinar damage have found no evidence that distracters interfere with performance (22-24), and one study reports reduced flanker interference from contralesional distracters (25). Pulvinar activation has nevertheless been reported using fMRI or positron emission tomography in healthy human observers during filtering tasks or other attentional paradigms (8,(26)(27)(28)(29)(30). The lack of distracter interference effects in human neuropsychological studies may reflect the use of behavioral tasks that measured the effects of response conflict, rather than perceptual selection of stimuli based on their behavioral salience.…”
mentioning
confidence: 99%